Mardi Gras Beads - MacCash, Doug (Book collections on Project MUSE., 2022)
"Beads are one of the great Crescent City symbols, as much a signifier of the city as a pot of scarlet crawfish or a jazzman's trumpet. They are New Orleans's version of the Hawaiian lei, strung around tourists and conventioneers' necks to demonstrate their enthusiasm for the city. As part of a series of novelty books about Louisiana culture and history, Mardi Gras Beads delves into the history of this iconic New Orleans artifact, exploring how Mardi Gras beads came to be in the first place and how they grew to have such an outsize presence in New Orleans celebrations. Beads are a big business based on valueless-ness. One hundred and thirty shipping containers, each filled with 40,000 pounds of Chinese-made beads and other baubles, arrive at New Orleans's biggest Mardi Gras throw importer each carnival season. That amounts to 2,600 tons of toss-able plastic trinkets. Beads are an unnatural part of the natural landscape, persistently dangling from the trees along parade routes like Spanish moss. They clutter the doorknobs of the city, sway beneath its rearview mirrors, test the load-bearing strength of its attic rafters and clog its all-important rainwater removal system. City employees removed 93,000 pounds of tangled beads from backed-up catch basins in 2018. Mardi Gras Beads traces the history of these parade trinkets from their origins in Twelfth Night festivities through the ascent of beads as the "premier parade catchable" by the Depression era. MacCash explores the manufacture of Mardi Gras beads by creators in places as far-flung as the Sudetenland, the Caribbean, and Japan, and traces the shift away from glass beads to the modern, disposable versions that clog up the city's trees, drains, and roads. Mardi Gras Beads concludes in the year of coronavirus, considering the future of biodegradable Mardi Gras beads in a city ever more threatened by the specter of climate change"--